Patient Reported Delays in Seeking Treatment for Tuberculosis among Adult and Pediatric TB Patients and TB Patients Co-Infected with HIV in Lima, Peru: A Qualitative Study - Paz-Soldan, Valerie A.; Alban, Rebecca E.; Dimos Jones, Christy; Powell, Amy R.; Oberhelman, Richard A. (Frontiers in Public Health, 2014)
Abstract: Tuberculosis (TB) remains a significant public health challenge worldwide, and particularly in Peru with one of the highest incidence rates in Latin America. TB patient behavior has a direct influence on whether a patient will receive timely diagnosis and successful treatment of their illness. Objectives: The objective was to understand the complex factors that can impact TB patient health seeking behavior. Methods: In-depth interviews were conducted with adult and parents of pediatric patients receiving TB treatment (n=43), within that group a sub-group was also co-infected with HIV (n=11). Results: Almost all of the study participants recognized delays in seeking either their child’s or their own diagnosis of their TB symptoms. The principal reasons for treatment-seeking delays were lack of knowledge and confusion of tuberculosis symptoms, fear and embarrassment of receiving a TB diagnosis, and a patient tendency to self-medicate prior to seeking formal medical attention. Conclusions: Health promotion activities that target patient delays have the potential to improve individual patient outcomes and mitigate the spread of TB at a community level.